Enhancing Mechanical Properties of Aluminum Matrix Composites Reinforced with Carbon Nanotubes: A Review of Fabrication Methods and Applications - Nabila Desi Rahmawati; Immanuel Simanjuntak; Fikri Muzhaffar; Ade Kurniawan; Judika Butar-butar; Logo, Damai Logo (Proklamasi 45 University, 2025)
This study reviews the fabrication methods and compositions of aluminum matrix composites reinforced with Carbon Nanotubes (CNTs), aiming to enhance the mechanical properties of aluminum composites. The methods analyzed include ball milling, spark plasma extrusion (SPE), and chemical vapor deposition (CVD), each showing unique advantages in improving tensile strength, hardness, wear resistance, and thermal conductivity. The study highlights significant findings, such as SPE's ability to address CNT agglomeration, ensuring a more homogeneous distribution, and increasing material density. Results also reveal the effectiveness of CNT coatings in improving electromagnetic shielding performance and thermal conductivity for extreme conditions. The significance of this research lies in identifying optimal fabrication techniques and compositions, offering valuable insights for advancing lightweight, high-strength materials in automotive, aerospace, and other industries. This study emphasizes the potential of Al-CNT composites as superior materials for industrial applications and the need for further exploration of hybrid fabrication methods and CNT types.